Pengaruh Penerapan Model Pembelajaran Group Investigation dan Motivasi Terhadap Hasil Belajar Siswa Kela VII SMP Dalam Pembelajaran IPA Terpadu Pada Materi Asam, Basa dan Garam - Susy Pransiska; Rayandra Asyhar; Asrial Asrial (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
This research aimed to determine the effect of group investigation learning  model and motivation on the students' learning result. The research employed a quasi experimental research with nonrandomized control group pretest-posttest design. The research used factorial design of 2x2. The population of this research was the first semester of seventh grade students. The sample used VII A and VII B class, samples were taken by using purposive sampling. The learning result data measured using of the tests and motivation data using of questionnaires. The data are analyzed using two-way(s) ANOVA. Test analysis showed that difference between post-test score of experiment class were higher than the control class. Based on the result, it can be concluded that: 1) the implementation of the group learning model investigation affect the students’ learning result, 2) motivation also influences the student learning result. 3) There is no interaction between the group investigation learning  model and motivation on the students' learning achievement.   Keywords: Group Investigation, Motivation and Learning Result.